2005
DOI: 10.1037/0278-6133.24.4.339
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Healthy Body Healthy Spirit Trial.

Abstract: Healthy Body Healthy Spirit was a multicomponent intervention to increase fruit and vegetable (F & V) consumption and physical activity (PA) delivered through Black churches. Sixteen churches were randomly assigned to 3 intervention conditions. At baseline, 1,056 individuals were recruited across the 16 churches, of which 906 (86%) were assessed at 1-year follow-up. Group 1 received standard educational materials, Group 2 received culturally targeted self-help nutrition and PA materials, and Group 3 received t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
240
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(252 citation statements)
references
References 38 publications
11
240
1
Order By: Relevance
“…Some studies used qualitative techniques such as participant or researcher observations [28,45,59,63], focus groups [43,48,68,69], and participant interviews or surveys. Others used quantitative techniques such as analyzing tracking and enrollment registries according to recruitment strategy [46,47,49].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies used qualitative techniques such as participant or researcher observations [28,45,59,63], focus groups [43,48,68,69], and participant interviews or surveys. Others used quantitative techniques such as analyzing tracking and enrollment registries according to recruitment strategy [46,47,49].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas only a handful of researchers have attempted to integrate MI into BWL treatment, other researchers (Bowen et al, 2002;Resnicow et al, 2001Resnicow et al, , 2004Resnicow et al, , 2005 have reported positive findings from trials using MI strategies as an adjunct to large-scale prevention programs aimed at improving dietary habits. Resnicow and colleagues (Resnicow et al, 2001(Resnicow et al, , 2004(Resnicow et al, , 2005, for example, have incorporated MI-informed phone calls into prevention programs aimed at promoting fruit and vegetable intake (Resnicow et al, 2001(Resnicow et al, , 2004(Resnicow et al, , 2005 for large groups of African-American churchgoers.…”
Section: Motivational Interviewing In Behavioral Weight Loss Treatmentmentioning
confidence: 99%
“…Resnicow and colleagues (Resnicow et al, 2001(Resnicow et al, , 2004(Resnicow et al, , 2005, for example, have incorporated MI-informed phone calls into prevention programs aimed at promoting fruit and vegetable intake (Resnicow et al, 2001(Resnicow et al, , 2004(Resnicow et al, , 2005 for large groups of African-American churchgoers. Results from studies of these programs indicated that groups receiving MI-informed phone calls reported significantly greater intake of fruits and vegetables at 6 months (Resnicow et al, 2004) and 1 year (Resnicow et al, 2001(Resnicow et al, , 2005 relative to those in a control intervention (Resnicow et al, 2001(Resnicow et al, , 2004(Resnicow et al, , 2005 and those receiving the same self-help materials but no MI phone calls (Resnicow et al, 2001(Resnicow et al, , 2005.…”
Section: Motivational Interviewing In Behavioral Weight Loss Treatmentmentioning
confidence: 99%
“…22,23 Additionally, the church has a history of involvement in activities to improve the health of African Americans and is an important source of support for caregivers of seriously ill patients. [24][25][26][27] Further, partnerships between hospices and churches may provide an opportunity for clergy to respond to concerns about hospice use related to spiritual beliefs. 23 Although much of the emphasis on health in the African American church has been related to health promotion and disease prevention, the findings of this study suggest that church-based activities to promote quality of care at the end of life may be growing; however, currently, there are few published reports of such initiatives.…”
Section: Discussionmentioning
confidence: 99%